Apolipoprotein E gene polymorphism in hypertension - Ibrahim, Wisam Nabeel; A.Talib, Norlelawati; Abdullah, Nor Zamzila; Aung, Nilar; Ku Zaifah, Norsidah (2013)
Essential hypertension is a common multifactorial disease of the cardiovascular system with significant morbidity and mortality (Trenk et al .,1999 ). It is believed that essential hypertension is caused by complex interactions between multiple environmental and genetic factors. Even though much is known about the environmental factors such as salt intake and exercise, but on the other hand the genetic factors that predispose individuals to hypertension are still poorly understood. It is also very clear from literatures that oxidative stress, atherosclerosis and endothelial dysfunction play an important role in the pathogenesis of experimental and human hypertension (Touyz et al., 2004). Apo lipoprotein E (Apo E) is a plasma protein which has shown a powerful antioxidant, anti atherosclerotic and endothelial protective properties that might protect from initiation and progression of hypertension. Apo E is synthesized mainly by the liver. It is the critical ligand in the plasma clearance of triglyceride and cholesterol-rich lipoproteins (chylomicron remnants, VLDL, intermediate density lipoproteins and LDL), (Mahley et al., 2000). The biological function of Apo E is highly effected by the polymorphism in its gene which is located on chromosome 19 and it’s polymorphism results in three common alleles of protein (Ԑ2, Ԑ3 and Ԑ4) (Mahley et al., 2011) . In which the Ԑ3 allele is the normal functional form while the Ԑ2 and Ԑ4 alleles are the dysfunctional forms which are associated with increased risk for atherosclerosis & oxidative stress (Mahley et al., 2011).